Epitope Targeting of Tertiary Protein Structure Enables Target‐Guided Synthesis of a Potent In‐Cell Inhibitor of Botulinum Neurotoxin1. (29th April 2015) - Farrow, Blake; Wong, Michelle; Malette, Jacquie; Lai, Bert; Deyle, Kaycie M.; Das, Samir; Nag, Arundhati; Agnew, Heather D.; Heath, James R.
Abstract Botulinum neurotoxin (BoNT) serotype A is the most lethal known toxin and has an occluded structure, which prevents direct inhibition of its active site before it enters the cytosol. Target‐guided synthesis by in situ click chemistry is combined with synthetic epitope targeting to exploit the tertiary structure of the BoNT protein as a landscape for assembling a competitive inhibitor. A substrate‐mimicking peptide macrocycle is used as a direct inhibitor of BoNT. An epitope‐targeting in situ click screen is utilized to identify a second peptide macrocycle ligand that binds to an epitope that, in the folded BoNT structure, is active‐site‐adjacent. A second in situ click screen identifies a molecular bridge between the two macrocycles. The resulting divalent inhibitor exhibits an in vitro inhibition constant of 165 pM against the BoNT/A catalytic chain. The inhibitor is carried into cells by the intact holotoxin, and demonstrates protection and rescue of BoNT intoxication in a human neuron model.